Combinatorial design for a conference: constructing a balanced three-parallel session schedule - Ibrahim, Haslinda; Ramli, Razamin; Hassan, Mohammad Hasnan (Taylor & Francis Group, 2008)
In this paper, we present some well known results in combinatorial design theory. Next, we will use these results to construct a balanced three-parallel session schedule for a conference.A conference normally contains a set of sessions (each one of them involving three fields) that has to be scheduled within a time period of k days. The problem consists of finding a balanced schedule for each field.